Propensity score matched comparison of SBRT versus IMRT for the treatment of localized prostate cancer - Oliai, Caspian (J Radiat Oncol, 2016)
OBJECTIVE: Stereotactic body radiation therapy (SBRT) is an attractive option for prostate cancer due to its short treatment duration and cost. In this report, we compare the efficacy and toxicity outcomes of prostate cancer patients treated with SBRT to those who received intensity-modulated radiation therapy (IMRT). METHODS: Two hundred sixty-three patients with localized prostate adenocarcinoma were included, ranging from clinically very low- to high-risk groups. We retrospectively compare consecutive patients treated with SBRT with consecutive patients treated with conventionally fractionated IMRT. For most patients, SBRT was delivered to a total dose of 36.25 Gy in five fractions and IMRT to 75.6 Gy in 42 fractions. To minimize selection bias, we perform propensity score analyses. RESULTS: The treatment groups became similar after propensity matching with absolute standard bias reduced to ≤0.19. For the first analysis, 5-year actuarial survival was 90.8 and 88.1 % in SBRT and IMRT groups, respectively (p = 0.7260), while FFBF was 88.7 and 95.5 %, respectively (p = 0.1720). For the second analysis (accounting for risk group), actuarial 5-year survival was 96.7 and 87.1 % in the SBRT and IMRT groups, respectively (p = 0.3025), while FFBF was 89.7 and 90.3 %, respectively (p = 0.6446). Toxicity did not exceed grade 3 in any of the studied patients. The highest recorded genitourinary toxicity at the time of latest follow-up was grade 2. CONCLUSION: Our data support the hypothesis that SBRT has non-inferior efficacy and toxicity rates as IMRT. Given the lower cost and convenience for patients, SBRT may be considered as an alternative treatment for localized prostate cancer.